FLORAE MALESIANAE PRAECURSORES XIV* A REVISION OF THE GENUS DIPLYCOSIA (ERICACEAE) - H. SLEUMER (Research Center for Biology, 1957)
In this revision of the nearly exclusively Malaysian genus Diplycosia Bl. 84 species and 12 varieties are distinguished, of which 17 new Malaysian species resp. 8 varieties and 2 extramalaysian species are described; 4 species have been reduced to varietal rank, 1 new name has been proposed. An index to specimens has been added.